Case report: Diagnosis of hereditary hemorrhagic telangiectasia (Osler Weber Rendu Syndrome) in a 23-year-old male presented with anemia and thrombocytopenia and its response to bevacizumab - Yunus, Hamza; Amin, Said; Haq, Furqan Ul; Ali, Waqar; Hamid, Tanveer; Ali, Wajid; Ullah, Basharat; Bai, Payal (Frontiers in Medicine, 2022)
Osler Weber Rendu Syndrome (OWS) is characterized by the development of abnormally dilated blood vessels which manifest as arteriovenous shunts (pulmonary, gastrointestinal, hepatic, cerebral) and mucocutaneous telangiectasias (lips, tongue, fingertips). It is an autosomal dominant disease with a defect in transforming growth factor beta superfamily genes. This defect results in increased angiogenesis and disruption of vessel wall integrity. The disease remains underreported, with occasional history of recurrent epistaxis, iron deficiency anemia, and gastrointestinal bleeding in moderate to severe cases. Diagnosis is based on clinical presentation and confirmed by genetic testing. Various local (nasal saline, air humidification, laser ablation, electric cauterization for epistaxis and endoscopic Argon Plasma Coagulation-APC for active GI bleed), surgical and systemic (tranexamic acid, antiangiogenic agents like bevacizumab and thalidomide) treatment options are used depending upon disease severity. Here we present a case with recurrent gastrointestinal bleeding refractory to endoscopic APC ablation and thalidomide and severe symptomatic anemia requiring multiple Packed Red Cell transfusions. The patient was ultimately started on bevacizumab, to which he had a good response and has remained in remission for 8 months as of now. This case emphasizes the need to have a low threshold of suspicion to diagnose HHT and start targeted therapy like bevacizumab early on in moderate to severe cases of HHT rather than just relying on temporizing palliative measures like ablation, cauterization, and tranexamic acid.